Epigenetic regulation of programmed cell death in hypoxia-induced pulmonary arterial hypertension - Jiang, Yuan; Song, Shasha; Liu, Jingxin; Zhang, Liyuan; Guo, Xiaofei; Lu, Jiayao; Li, Lie; Yang, Chao; Fu, Qiang; Zeng, Bin (Frontiers in Immunology, 2023)
Pulmonary arterial hypertension (PAH) is a severe progressive disease that may cause early right ventricular failure and eventual cardiac failure. The pathogenesis of PAH involves endothelial dysfunction, aberrant proliferation of pulmonary artery smooth muscle cells (PASMCs), and vascular fibrosis. Hypoxia has been shown to induce elevated secretion of vascular endothelial growth factor (VEGF), leading to the development of hypoxic PAH. However, the molecular mechanisms underlying hypoxic PAH remain incompletely understood. Programmed cell death (PCD) is a natural cell death and regulated by certain genes. Emerging evidence suggests that apoptotic resistance contributes to the development of PAH. Moreover, several novel types of PCD, such as autophagy, pyroptosis and ferroptosis have been reported to be involved in the development of PAH. Additionally, multiple diverse epigenetic mechanisms including RNA methylation, DNA methylation, histone modification and the non-coding RNA molecules mediated processes have been strongly linked to the development of PAH. These epigenetic modifications affect the expression of genes which produce important changes in cellular biological processes, including PCD. Consequently, better understanding the PCD processes and epigenetic modification involved in PAH will provide novel, specific therapeutic strategies for diagnosis and treatment. In this review, we aim to discuss recent advances in epigenetic mechanisms and elucidate the role of epigenetic modifications in regulating PCD in hypoxia-induced PAH.